Correlation Between Reaction Speed and Forehand Smash Performance in Table Tennis Among High School Students at SMA Negeri 17 Medan - Karo Karo, Alan Alfiansyah Putra; Sandika, Chery; Syahputra, Raynaldo (Pusat Pengembangan Olahraga Universitas Pahlawan, 2024)
Introduction: Reaction speed is a fundamental motor skill that significantly influences athletic performance in racket sports, particularly in table tennis where rapid decision-making and execution are crucial. The forehand smash represents one of the most decisive offensive techniques in table tennis, requiring optimal coordination between cognitive processing and motor execution. Purpose of the study: This study aimed to investigate the correlation between reaction speed and forehand smash performance among male high school students, providing insights into the neuromuscular factors that contribute to table tennis proficiency. Materials and methods: Twenty-eight male students from SMA Negeri 17 Medan (age: 16.2 ± 0.8 years) participated in this cross-sectional study. Reaction speed was measured using a digital reaction timer, while forehand smash performance was evaluated through accuracy and speed assessments. Data were analyzed using Pearson correlation coefficient and descriptive statistics via SPSS version 27. Results: A significant moderate positive correlation was found between reaction speed and forehand smash performance (r = 0.612, p < 0.01). Students with faster reaction times (mean: 0.187 ± 0.032 seconds) demonstrated superior forehand smash accuracy (78.4 ± 12.3%) and ball velocity (15.2 ± 2.1 m/s) compared to those with slower reaction times. Conclusions: Reaction speed significantly correlates with forehand smash performance in table tennis among high school students. These findings suggest that incorporating reaction speed training into table tennis coaching programs may enhance offensive playing capabilities.